Scenario-based traffic forecasts for the routes between the PENTA ports in 2020 - Lappalainen, Anssi (Publications of the Centre for Maritime Studies, University of Turku A 65, 2014)
Maritime transport is the foundation for trade in the Baltic Sea area. It represents over 15% of the world’s cargo traffic and it is predicted to increase by over 100% in the future. There are currently over 2,000 ships sailing on the Baltic Sea and both the number and the size of ships have been growing in recent years. Due to the importance of maritime traffic in the Baltic Sea Region, ports have to be ready to face future challenges and adapt to the changing operational environment. The companies within the transportation industry – in this context ports, shipowners and logistics companies – compete continuously and although the number of companies in the business is not particularly substantial because the products offered are very similar, other motives for managing the supply chain arise. The factors creating competitive advantage are often financial and related to cost efficiency, but geographical location, road infrastructure in the hinterland and vessel connections are among the most important factors. The PENTA project focuses on adding openness, transparency and sharing knowledge and information, so that the challenges of the future can be better addressed with regard to cooperation. This report presents three scenario-based traffic forecasts for routes between the PENTA ports in 2020. The chosen methodology is PESTE, in which the focus in on economic factors affecting future traffic flows. The report further analyses the findings and results of the first PENTA WP2 report “Drivers of demand in cargo and passenger traffic between PENTA ports” and utilises the same material, which was obtained through interviews and mail surveys.

Meriliikenne on Itämeren alueen kaupankäynnin perusta. Se on kooltaan noin 15 % maailman rahtiliikenteestä ja sen ennustetaan kaksinkertaistuvan tulevaisuudessa. Itämerellä liikennöi joka hetki yli 2000 alusta ja niiden määrät sekä koot ovat kasvaneet viime vuosina. Johtuen meriliikenteen suuresta merkityksestä Itämeren alueella, on satamien oltava valmiita kohtaamaan tulevaisuuden haasteita sekä sopeutumaan muuttuvaan toimintaympäristöön. Kuljetusteollisuuden yritykset – tässä yhteydessä satamat, varustamot ja kuljetusliikkeet – kilpailevat jatkuvasti keskenään. Koska alalla olevien yritysten lukumäärä on suhteellisen pieni ja tarjotut palvelut sekä tuotteet ovat vain hieman toisistaan poikkeavia, nousevat muut motiivit esille toimitusketjua johdettaessa. Kilpailuetua luovat tekijät ovat usein taloudellisia ja liittyvät kustannustehokkuuteen mutta sataman maantieteellinen sijainti, takamaan tieverkosto ja alusten liikenneyhteydet kuuluvat myös tärkeimpiin tekijöihin. PENTA projekti keskittyy avoimuuden ja läpinäkyvyyden lisäämiseen, sekä tiedon ja informaation jakamiseen, jotta tulevaisuuden haasteisiin pystytään varautumaan paremmin yhteistyöllä. Tämä raportti esittää kolme skenaariopohjaista liikenne-ennustetta PENTA satamien välisille reiteille vuonna 2020. Valittuna metodologiana käytetään PESTE-analyysia, jossa pääpaino on taloudellisilla tekijöillä tulevaisuutta muokkaavina tekijöinä. Raportti analysoi tarkemmin ensimmäisen PENTA WP2-raportin ”Drivers of demand in cargo and passenger traffic between PENTA ports” tuloksia ja käyttää hyväkseen samaa materiaalia, joka hankittiin haastatteluilla ja sähköpostikyselyillä.